Thermal performance enhancement in perforated baffled annuli by nanoporous graphene non-Newtonian nanofluid. (25th February 2020) - Ghanbari, Shahin; Javaherdeh, Kourosh
Highlights: Nanoporous graphene nanofluid was used along with circular perforated baffles. Adding graphene enhanced the thermal performance by 16% in a plain annular tube. Nusselt number increased by 53.7% by the circular perforated baffles and nanofluid. Thermal performance was found to be dependent on the baffles holes number. Abstract: This study investigated the convective heat transfer and pressure drop of non-Newtonian nanoporous graphene nanofluids. The nanoporous graphene nanofluids were prepared using different concentrations of nanoparticles (i.e. 0.05, 0.1, and 0.2 wt%) in an aqueous solution of carboxymethyl cellulose, and the thermophysical and rheological properties were evaluated accordingly. Four types of circular perforated baffles with different hole numbers were designed and manufactured. The Nusselt number, friction factor, and thermal performance factor ( TPF ) were calculated for the nanofluid and the base fluid flows by installing the baffles and were compared to those of the plain annular tube. The measurements showed that adding 0.2 wt% nanoporous graphene to the base solution led to enhancements of 12.4 and 39.4% in the thermal conductivity and the average heat transfer coefficient, respectively. The results indicated that by simultaneously using non-Newtonian nanoporous graphene nanofluid and perforated circular baffles, the average TPF value could be enhanced by 29% in the studied turbulence regime. These significant conclusions can be exploited to design highly efficient thermal systems possessing much better thermal efficiency.